PENGARUH MEDIA INTERAKTIF POWERPOINT MATERI KEBERAGAMAN SUKU BANGSA DAN BUDAYA DI INDONESIA UNTUK MENGEMBANGKAN HASIL BELAJAR SISWA KELAS IV (EMPAT) SD - Icha Tantri Lestari; Imamudin; Munawaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Quantitative research is a method used to answer research problems related to data in the form of numbers and statistical programs. This study aims to determine the effect of using interactive PowerPoint media to develop the learning outcomes of fourth-grade elementary school students on the material of ethnic and cultural diversity in Indonesia. This study uses data collection techniques including pretest and posttest tests, questionnaires, documentation. The type of research